Impact Analysis of Temperature Effects on the Performance of the Pick-Up Ion Analyzer - Yu Cao; Yuzhu Zhang; Xiaodong Peng; Changbin Xue; Bin Su; Yiming Zhu (Aerospace)
In deep-space exploration, Pickup Ion Analyzers (PUIAs) operate under varying thermal environments in orbit, where thermally induced stress–deformation coupling may severely degrade their performance and long-term stability. To address temperature field analysis for in-orbit PUIAs, in this study, we propose a coupled simulation framework integrating external heat flux, parallel temperature field calculation, and thermoelastic deformation analysis, establishing a systematic link from thermal inputs to performance analysis. Based on external heat flux results, a parallel LU decomposition algorithm reduced the computational time from 11.8 h to 2.9 h for rapid temperature field solutions. At 38 astronomical units (AUs), the instrument’s temperature distribution ranged from −45 °C to 51.13 °C, with simulation errors compared to COMSOL simulations meeting engineering accuracy requirements. Maximum thermoelastic deformation induced by thermal gradients reached 0.110 mm. Performance degradation due to deformation in key metrics—including ion energy resolution, angular resolution, detection field-of-view, geometric factor, and mass resolution—was below 7.2%. This research improves the computational efficiency of the temperature field and systematically quantifies temperature effects on PUIA performance in deep-space environments, and the proposed methodology could provide technical support for optimizing on-orbit thermal management strategies.